Views and experiences of unemployed youth graduates : a case study of the Polokwane area, Limpopo Province, South Africa - Mokgohloa, Dolores (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil) -- University of Stellenbosch, 2006.